The Impacts of Fiscal Openness - de Renzio, Paola; Wehner, Joachim (Published by Oxford University Press on behalf of the World Bank, 2019)
Fiscal transparency and participation in government budgeting are widely promoted, yet claims about their benefits are rarely based on convincing evidence. We provide the first systematic review covering 38 empirical studies published between 1991 and early 2015. Increased budgetary disclosure and participation—which we call “fiscal openness”—are consistently associated with improvements in the quality of the budget, as well as governance and development outcomes. Only a handful of studies, however, convincingly identify causal effects, in the form of reduced corruption, enhanced electoral accountability, and improved allocation of resources. We highlight gaps and set out a research agenda that consists of: (a) disaggregating broad measures of budget transparency to uncover which specific disclosures are related to outcomes; (b) tracing causal mechanisms to connect fiscal openness interventions with ultimate impacts on human development; (c) investigating the relative effectiveness of alternative interventions; (d) examining the relationship between transparency and participation; and (e) clarifying the contextual conditions that support particular interventions.